2002
DOI: 10.1364/oe.10.000609
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of ultra-flattened dispersion in photonic crystal fibers

Abstract: We demonstrate photonic crystal fibers with ultra-flattened, near zero dispersion. Two micro-structured fibers showing dispersion of 0 +/- 0.6 ps/nm.km from 1.24 microm-1.44 microm wavelength and 0 +/- 1.2 ps/nm.km over 1 microm-1.6 microm wavelength have been measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
150
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(153 citation statements)
references
References 12 publications
2
150
0
1
Order By: Relevance
“…The proposed method has been investigated by using conventional fibers and ultra-flattened dispersion photonic crystal fibers (PCFs) [5]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method has been investigated by using conventional fibers and ultra-flattened dispersion photonic crystal fibers (PCFs) [5]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In optical fibers, a high nonlinear coefficient can be achieved by increasing the nonlinearity of core material such as with high Gedoping [1] or by improving the index contrast to obtain a better power confinement [2]. On the other hand, a low GVD near the pump wavelength had been succeeded by moving the zero-dispersion wavelength (ZDW) toward 800 and 1550-nm wavelength to close to the high-peak-power pump wavelength for tapered fiber [2] and the photonic crystal fiber [3], respectively. However, the high dispersion slope near the ZDW of silica fibers gives rise to a very limiting useful bandwidth as the silica fiber has a very high phonon energy with its ZDW occurring at around 1300 nm.…”
Section: Introductionmentioning
confidence: 99%
“…However, these basic topologies are limited to single frequency operation, and, recently, several studies are reported regarding dual-or multiband operation of impedance matching networks. So far, most of the dual-band impedance transformers are based on the two-section cascaded transmission line structure [2][3][4][5]. They are basically a special case of the Chebyshev multisection transformers with equal-length transmission line sections [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various index guiding hexagonal PCFs with remarkable dispersion properties (Wu and Chao 2005;Ferrando et al 2000;Ferrando et al 2001;Reeves et al 2002;Poletti et al 2005;Saitoh, Florous, and Koshiba 2005;Saitoh et al 2003) have been reported to date. The fabrication issue, more specifically the fabrication tolerance of these intriguing designs, is also crucial because in a standard fiber draw 1% variation in the fiber diameter occurs unavoidably during the fabrication process (Reeves et al 2002). As a result, roughly an accuracy of order AE1 to AE2% will be required to ensure the overall dispersion flatness (near zero dispersion slopes) with reasonable accuracy (Poletti et al 2005).…”
Section: Introductionmentioning
confidence: 99%